2006
DOI: 10.1186/1744-8069-2-24
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms in Monoamine Neurotransmitter Systems Show Only Weak Association with Acute Post-Surgical Pain in Humans

Abstract: Background: Candidate gene studies on the basis of biological hypotheses have been a practical approach to identify relevant genetic variation in complex traits. Based on previous reports and the roles in pain pathways, we have examined the effects of variations of loci in the genes of monoamine neurotransmitter systems including metabolizing enzymes, receptors and transporters on acute clinical pain responses in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 43 publications
3
97
0
3
Order By: Relevance
“…We selected the COMT gene because of its high priority candidate rating (Belfer et al, 2004) and its previous influence on pain perception for healthy subjects (Zubieta et al, 2003;Diatchenko et al, 2005Diatchenko et al, , 2006. The influence of COMT genotype for clinically relevant phenotypes has been questioned in the literature (Kim et al, 2006), but our data suggested that COMT diplotype had an influence on pain ratings, at least when determined by LPS and APS/HPS groups.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…We selected the COMT gene because of its high priority candidate rating (Belfer et al, 2004) and its previous influence on pain perception for healthy subjects (Zubieta et al, 2003;Diatchenko et al, 2005Diatchenko et al, , 2006. The influence of COMT genotype for clinically relevant phenotypes has been questioned in the literature (Kim et al, 2006), but our data suggested that COMT diplotype had an influence on pain ratings, at least when determined by LPS and APS/HPS groups.…”
Section: Discussionmentioning
confidence: 57%
“…This assertion was confirmed in healthy volunteers as μ-opioid receptor binding potential and activation were predictably associated with a COMT gene single nucleotide polymorphism (SNP) at codon 158 (Zubieta et al, 2003) and experimental pain sensitivity was associated with COMT haplotypes (Diatchenko et al, 2005. In contrast, other studies have found no association with COMT genotype and pain sensitivity in healthy volunteers (Kim et al, 2004) or weak associations in a post-surgical pain model (Kim et al, 2006).…”
Section: Introductionmentioning
confidence: 60%
“…47 We considered COMT genotype in this study because of its high-priority candidate rating 11 and its previous influence on pain perception for healthy participants, 13-15 and also those seeking surgical treatment for shoulder pain. 2 We did not detect a main effect for COMT genotype in the current study, however, our primary hypothesis did not involve testing main effects of COMT genotype.…”
Section: Discussionmentioning
confidence: 99%
“…2). [20][21][22][23][24][25][26] However, not all the evidence from these gene-pain studies concurs, 27 and it is therefore premature to use gene-mapping to predict and treat pain conditions.…”
Section: Agementioning
confidence: 99%